Dyslipidemia, Diet and Physical Exercise in Children on Treatment With Antiretroviral Medication in El Salvador: A Cross-sectional Study. Issue 10 (October 2016) - Sonego, Michela; Sagrado, Maria José; Escobar, Gustavo; Lazzerini, Marzia; Rivas, Estefanie; Martín-Cañavate, Rocio; Pérez de López, Elsy; Ayala, Sandra; Castaneda, Luis; Aparicio, Pilar; Custodio, Estefanía
Abstract : Background: Dyslipidemias are common in HIV-infected children, especially if treated with protease inhibitors, but there are few data on how to treat dyslipidemias in this population. We estimated the dyslipidemia prevalence and its association with treatment, diet and physical exercise in children on antiretroviral treatment at the El Salvador reference center for pediatric HIV care (CENID). Methods: Information was gathered regarding socio-demographic characteristics, treatment, diet and physical activity of 173 children aged 5–18 years and receiving antiretroviral therapy. Triglycerides, total cholesterol, low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), viral load and CD4 T-lymphocytes were measured. Abnormal concentrations were defined as triglycerides ≥130 mg/dL in 10- to 18-year olds and ≥100 mg/dL in <10-year olds; total cholesterol ≥200 mg/dL; LDL-C ≥130 mg/dL and HDL-C ⩽35 mg/dL. We adjusted 4 different multivariate models to assess the independent association of each type of dyslipidemia with protease inhibitors, diet and physical exercise. Results: Of the 173 children, 83 (48%) had hypertriglyceridemia and 25 (14.5%) hypercholesterolemia. High LDL-C concentrations were observed in 17 children (9.8%) and low HDL-C in 38 (22%). Treatment with protease inhibitors was significantly associated with hypertriglyceridemia [prevalence ratio (PR) 2.8; 95% confidence interval (CI): 2.0–3.8] and hypercholesterolemia (PR 9.0; 95% CI: 3.6–22.2). Higher adherence to a "high fat/sugar diet" was associated with hypercholesterolemia (PR 1.6; 95% CI: 1.1–2.3) and high LDL-C (PR 1.7; 95% CI: 1.0–2.9). Compared with those exercising <3 times/week, children exercising ≥7 times were less likely to have low HDL-C (PR = 0.4; 95% CI: 0.2–0.7). Conclusions: These results suggest that a healthy diet and exercise habits can contribute to controlling some aspects of the lipid profile in this population. Abstract : Supplemental Digital Content is available in the text.